90Sr specific activity of teeth of abandoned cattle after the Fukushima accident – teeth as an indicator of environmental pollution. (March 2018) - Koarai, Kazuma; Kino, Yasushi; Takahashi, Atsushi; Suzuki, Toshihiko; Shimizu, Yoshinaka; Chiba, Mirei; Osaka, Ken; Sasaki, Keiichi; Urushihara, Yusuke; Fukuda, Tomokazu; Isogai, Emiko; Yamashiro, Hideaki; et al.
Abstract: 90 Sr specific activity in the teeth of young cattle that were abandoned in Kawauchi village and Okuma town located in the former evacuation areas of the Fukushima-Daiichi Nuclear Power Plant (FNPP) accident were measured. Additionally, specific activity in contaminated surface soils sampled from the same area was measured. (1) All cattle teeth examined were contaminated with 90 Sr. The specific activity, however, varied depending on the developmental stage of the teeth during the FNPP accident; teeth that had started development before the accident exhibited comparatively lower values, while teeth developed mainly after the accident showed higher values. (2) Values of 90 Sr-specific activity in teeth formed after the FNPP accident were higher than those of the bulk soil but similar to those in the exchangeable fraction (water and CH3 COONH4 soluble fractions) of the soil. The findings suggest that 90 Sr was incorporated into the teeth during the process of development, and that 90 Sr in the soluble and/or leachable fractions of the soil might migrate into teeth and contribute to the amount of 90 Sr in the teeth. Thus, the concentration of 90 Sr in teeth formed after the FNPP accident might reflect the extent of 90 Sr pollution in the environment. Highlights: 90 Sr in cattle teeth was determined after the Fukushima accident. 90 Sr was efficiently incorporated into the teeth at development stages. 90 Sr specific activity of aqueous extract was higher than that of soil. Water soluble 90 Sr was incorporated into the cattle and accumulated. Sr transfer is eliminated compared to Ca in the migration route.